Comparison of pathological outcomes between robotic rectal cancer surgery and laparoscopic rectal cancer surgery: A meta‐analysis based on seven randomized controlled trials. Issue 5 (22nd August 2019) - Liao, Guixiang; Zhao, Zhihong; Deng, Haijun; Li, Xianming
Abstract: Objective: To compare the pathologic outcomes between robotic‐assisted rectal cancer surgery (RRCS) and laparoscopic rectal cancer surgery (LRCS) based on randomized controlled trials (RCTs). Methods: Electronic databases were searched from their inception to 7 October 2018, for RCTs involving a comparison between RRCS and LRCS. Positive circumferential resection margin (CRM), distance to the distal margin, proximal margin, the rate of complete mesorectal excision, and harvested lymph nodes were interesting of outcomes. Results: The positive CRM, proximal margin, and rate of complete mesorectal excision were comparable between the two techniques. RRCS resulted in better outcomes for the distance to the distal margin (mean difference: 0.83 cm, 95% confidence interval, 0.29‐1.37, P = .003). Conclusions: The pathologic outcomes associated with the two approaches were comparable, with RRCS showing better outcomes for the distance to the distal margin. However, additional well‐designed studies are needed to assess whether the benefits of pathologic outcomes improve survival outcomes.